Biphasic apatite-carbon materials derived from pyrolysed fish bones for effective adsorption of persistent pollutants and heavy metals. Issue 5 (October 2017) - Piccirillo, C.; Moreira, I.S.; Novais, R.M.; Fernandes, A.J.S.; Pullar, R.C.; Castro, P.M.L.
Graphical abstract: Highlights: Biochar-like materials were prepared through pyrolysis of cod fish bones. They were tested to adsorb heavy metal and pharmaceutical persistent pollutants. Results showed different efficiency according to the pyrolysis temperature. Different kinetic mechanisms were observed for heavy metal (Pb(II)) and organics. Apatite and graphite were determinant in metal or organics adsorption respectively. Abstract: Biphasic apatite-carbon biochar-type materials were prepared from pyrolysed cod fish bones and were assessed for the adsorption of persistent organic pollutants (pharmaceuticals diclofenac and fluoxetine), and heavy metals (Pb(II)). The materials, prepared with a simple pyrolysis process at different temperatures (200–1000 °C), were characterised with XRD, FTIR, Raman and SEM. Results showed that the pyrolysis temperature had a significant effect on the features/composition of the materials: up to 800 °C, carbonate apatite Ca10 (PO4 )6 (CO3 ) was the main component, while for higher temperatures oxyapatite Ca10 (PO4 )6 O was the dominant phase. Graphitic carbon was also detected. The mixed apatite-carbon products (bone char) exhibited high adsorption efficiency. Graphite carbon was the main adsorber for the pharmaceuticals, the best performing material being that pyrolysed at 1000 °C. Xm values of 43.29 and 55.87 mg/g were observed (Langmuir fitting), while KF values of 5.40 and 12.53 (mg/g)(L/mg) n F were obtained with the Freundhlich model (diclofenac and fluoxetine respectively). This is the first time that a biochar-like material has been used for fluoxetine adsorption. For Pb (II), the powder pyrolysed at 600 °C was the most effective, with the apatite playing a key role (Xm = 714.24 mg/g). This work shows that a by-product of the fish industry could be converted into efficient materials for environmental remediation; according to the pyrolysis conditions, powders effective in the removal of either organics or heavy metals can be obtained. Moreover, with pyrolysis at intermediate temperatures, materials capable of adsorbing both kinds of pollutants can be produced, even if less efficient.